Owen's Marshmallow Chick - Henkes, Kevin (New York, : HarperFestival, 2002)
Owen adores Easter and proclaims each item in his basket his favorite and eats them immediately, until he sees the chicken, that is the same color as his blanket.
a"A Greenwillow book"--Cover.
aOn board pages.
Keywords: Easter -- Fiction; Mice -- Fiction; Candy -- Fiction; Friendship -- Fiction